2020
DOI: 10.1371/journal.pone.0242143
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater diatom biomonitoring through benthic kick-net metabarcoding

Abstract: Biomonitoring is an essential tool for assessing ecological conditions and informing management strategies. The application of DNA metabarcoding and high throughput sequencing has improved data quantity and resolution for biomonitoring of taxa such as macroinvertebrates, yet, there remains the need to optimise these methods for other taxonomic groups. Diatoms have a longstanding history in freshwater biomonitoring as bioindicators of water quality status. However, multi-substrate periphyton collection, a commo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…This can be done in connection with conventional kick sampling, but perhaps also as a standalone index, as has been suggested for marine macroinvertebrate monitoring using bulk metabarcoding (Aylagas et al, 2014). There are still many avenues to be explored for macroinvertebrate eDNA detection, such as taxonomy-free approaches with machine learning as has been done with diatom eDNA metabarcoding (Apothéloz-Perret-Gentil et al, 2020), and eDNA sampling could even help alleviate the need for multiple different sampling events, as the same sample can be used to infer multiple stream indices across different taxa (Maitland et al, 2020).…”
Section: Perspectives For Freshwater Ecology Research and Biomonitoringmentioning
confidence: 99%
“…This can be done in connection with conventional kick sampling, but perhaps also as a standalone index, as has been suggested for marine macroinvertebrate monitoring using bulk metabarcoding (Aylagas et al, 2014). There are still many avenues to be explored for macroinvertebrate eDNA detection, such as taxonomy-free approaches with machine learning as has been done with diatom eDNA metabarcoding (Apothéloz-Perret-Gentil et al, 2020), and eDNA sampling could even help alleviate the need for multiple different sampling events, as the same sample can be used to infer multiple stream indices across different taxa (Maitland et al, 2020).…”
Section: Perspectives For Freshwater Ecology Research and Biomonitoringmentioning
confidence: 99%
“…Nevertheless, the complexity of diatom responses to environmental variables and the potential for regional variation remind us that diatom-based indices should be applied with careful consideration of local conditions and, when necessary, adapted to specific regions or river types to ensure accurate water quality assessment. In this regard, DNA metabarcoding and high-throughput sequencing are being applied to diatom biomonitoring, improving data quantity and resolution (Maitland et al 2020 ). Overall, diatom-based indices, either based on DNA metabarcoding techniques or traditional microscopy-based methods, have advanced the state-of-the-art in river biomonitoring using diatoms as indicators of water quality (Goldenberg-Vilar et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a mixed assemblage offers opportunities and challenges for using eDNA for ecological monitoring when compared to biofilm DNA. Metabarcoding studies comparing the effect of sample substrate on measured algal assemblages are sparse, but Maitland et al (2020) compared stream diatom assemblages from rock scrapes, sediment, macrophytes, leaf litter, and kick‐net sampling (a method traditionally used to target benthic macroinvertebrates) and found no significant differences in assemblage composition – though a higher number of planktonic diatom species were detected using kick‐netting than rock scrapes. Meanwhile, Hajibabaei et al (2019) found that benthic macroinvertebrate assemblages strongly differed between filtered water and kick‐net benthos samples, demonstrating that sample substrate has the potential to influence DNA‐based biomonitoring results.…”
Section: Discussionmentioning
confidence: 99%